2013
DOI: 10.1186/2193-1801-2-16
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality and ability on undergraduate teamwork and team performance

Abstract: The ability to work effectively on a team is highly valued by employers, and collaboration among students can lead to intrinsic motivation, increased persistence, and greater transferability of skills. Moreover, innovation often arises from multidisciplinary teamwork. The influence of personality and ability on undergraduate teamwork and performance is not comprehensively understood. An investigation was undertaken to explore correlations between team outcomes, personality measures and ability in an undergradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
2
46
0
4
Order By: Relevance
“…Previous studies found that graduate engineering and business student teams diverse in openness exhibited more creativity on their innovation management class project [2]. The gender diversity of the team can affect how team members interact with one another, thereby affecting the performance of that team.…”
Section: Team Diversitymentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies found that graduate engineering and business student teams diverse in openness exhibited more creativity on their innovation management class project [2]. The gender diversity of the team can affect how team members interact with one another, thereby affecting the performance of that team.…”
Section: Team Diversitymentioning
confidence: 99%
“…Knowledge of team member's personality types helps to understand team member behavior, managing the dynamics of the team and to know how team members interact well in a group setting to accomplish the task [35]. Previous studies found correlations between individual personality and performance on a team [2] [11]. Differences in personality type of the members on a team have the potential to improve team effectiveness by increasing diversity of perspectives and behaviors [11].…”
Section: Team Formation Personality and Team Performancementioning
confidence: 99%
See 3 more Smart Citations